Protecting human rights in the European Union : problems and prospective scenarios - Schiappa-Pietra, Oscar (2004)
The purpose ofthe paper is thus, on one hand, to shed light on how the judicial interinstitutional tensions, and more importantly the power-bargaining between the European institutions and States and the normative developments within the EU, have evolved to accommodate divergent interests and values; and, on the other, to reflect on how this experience might project itself into the ongoing Community and constitutional process in Europe.